Morphological and ecological revision of Himantariella scutellaris Brolemann, 1926(Chilopoda: Geophilomorpha: Himantariidae) - Cabanillas, David; Serra, Antoni; López-Alonso, Ricardo; Carbonell, Rafael; Robla, Jairo (Zootaxa, 2023)
Himantariella scutellaris Brolemann, 1926 has previously been considered a French endemic species from the eastern Pyrenees. New collecting data from the Spanish Pre-Pyrenees, the Prelitoral Mountain Range and the Cantabric Region, make it possible to expand its known distribution to the northern Iberian Peninsula. Intraspecific variability, habitat preferences and ethology are assessed for the first time. New figures on the morphology of H. scutellaris and identification keys for the European Himantariidae with terminal pore-fields are provided. Results showed a wider range of morphological variability than previously reported and allowed to update the diagnostic characters needed for identification. Additionally, results showed monticolous, synanthropic and nocturnal habits for the Iberian populations and suggest that H. scutellaris is a common species at a local scale. Finally, morphology and ecology of H. scutellaris from the Iberian Peninsula and the Pyrenees are discussed in depth.